Novell® Open Enterprise Server Administrator's Handbook SUSE® LINUX® Edition - Latimer, Mike; Harris, Jeffrey (Sams, 2005)
As an administrator of a Novell® Open Enterprise Server (OES) on a SUSE® LINUX system, you are looking for ways to leverage it as a platform for delivering Novell's robust network services. Look no further. Novell Open Enterprise Server Administrator's Handbook, SUSE LINUX Edition provides you with the information that you need to take advantage of Novell rich array of nework management tools on a SUSE-powered system. By focusing on the implementation of OES on the SUSE LINUX platform, administrators learn how to integrate the benefits of OES in an existing environment. While this is not a reference work for network theory, protocols or architectures, it will provide the reader with a brief introduction to the concepts necessary to understand features of the product. Novell Open Enterprise Server Administrator's Handbook, SUSE LINUX Edition provides you with quick access to the information about the technologies, concepts and techniques that you need to get the job done.